Bacterial Leaf Spot of Cucurbits - Kiersten Fullem; Mathews L. Paret; Jeffrey B. Jones (EDIS)
This publication is intended to provide information on the disease bacterial leaf spot of cucurbits, its epidemiology, and management to cucurbit growers in the southeastern United States. Written by Kiersten Fullem, Mathews L. Paret, and Jeffrey B. Jones, and published by the UF/IFAS Plant Pathology Department, March 2024.